Comprehensive Analysis of LncRNA AC010789.1 Delays Androgenic Alopecia Progression by Targeting MicroRNA-21 and the Wnt/β-Catenin Signaling Pathway in Hair Follicle Stem Cells - Xiong, Jiachao; Wu, Baojin; Hou, Qiang; Huang, Xin; Jia, Lingling; Li, Yufei; Jiang, Hua (Frontiers in Genetics, 2022)
Background: Androgen alopecia (AGA), the most common type of alopecia worldwide, is become an important medical and social issue. Accumulating evidence indicates that long non-coding RNAs (lncRNAs) play crucial roles in the progression of various human diseases, including AGA. However, the potential roles of lncRNAs in hair follicle stem cells (HFSCs) and their subsequent relevance for AGA have not been fully elucidated. The current study aimed to explore the function and molecular mechanism of the lncRNA AC010789.1 in AGA progression. Methods: We investigated the expression levels of AC010789.1 in AGA scalp tissues compared to normal tissues and explored the underlying mechanisms using bioinformatics. HFSCs were then isolated from hair follicles of patients with AGA, and an AC010789.1-overexpressing HFSC line was produced and verified. Quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting were performed to verify the molecular mechanisms involved. Results: AC010789.1 overexpression promoted the proliferation and differentiation of HFSCs. Mechanistically, we demonstrated that AC010789.1 overexpression promotes the biological function of HFSCs by downregulating miR-21-5p and TGF-1 but upregulating the Wnt/-catenin signaling pathway. Conclusion: These results reveal that overexpression of AC010789.1 suppresses AGA progression via downregulation of hsa-miR-21-5p and TGF-1 and promotion of the Wnt/-catenin signaling pathway, highlighting a potentially promising strategy for AGA treatment.